Enhanced cell‐surface display and secretory production of cellulolytic enzymes with Saccharomyces cerevisiae Sed1 signal peptide. Issue 11 (3rd June 2016) - Inokuma, Kentaro; Bamba, Takahiro; Ishii, Jun; Ito, Yoichiro; Hasunuma, Tomohisa; Kondo, Akihiko
ABSTRACT: Recombinant yeast strains displaying aheterologous cellulolytic enzymes on their cell surfaces using a glycosylphosphatidylinositol (GPI) anchoring system are a promising strategy for bioethanol production from lignocellulosic materials. A crucial step for cell wall localization of the enzymes is the intracellular transport of proteins in yeast cells. Therefore, the addition of a highly efficient secretion signal sequence is important to increase the amount of the enzymes on the yeast cell surface. In this study, we demonstrated the effectiveness of a novel signal peptide (SP) sequence derived from the Saccharomyces cerevisiae SED1 gene for cell‐surface display and secretory production of cellulolytic enzymes. Gene cassettes with SP sequences derived from S. cerevisiae SED1 ( SED1 SP), Rhizopus oryzae glucoamylase ( GLUA SP), and S. cerevisiae α‐mating pheromone ( MFα1 SP) were constructed for cell‐surface display of Aspergillus aculeatus β‐glucosidase (BGL1) and Trichoderma reesei endoglucanase II (EGII). These gene cassettes were integrated into the S. cerevisiae genome. The recombinant strains with the SED1 SP showed higher cell‐surface BGL and EG activities than those with the conventional SP sequences ( GLUA SP and MFα1 SP). The novel SP sequence also improved the secretory production of BGL and EG in S. cerevisiae . The extracellular BGL activity of the recombinant strains with the SED1 SP was 1.3‐ and 1.9‐fold higher than the GLUA SP and MFα1 SP strains, respectively. Moreover, the utilization of SED1 SP successfully enhanced the secretory production of BGL in Pichia pastoris . The utilization of the novel SP sequence is a promising option for highly efficient cell‐surface display and secretory production of heterologous proteins in various yeast species. Biotechnol. Bioeng. 2016;113: 2358–2366. © 2016 Wiley Periodicals, Inc. Abstract : The effectiveness of a novel signal peptide (SP) sequence derived from the Saccharomyces cerevisiae SED1 gene ( SED1 SP) for cell‐surface display and secretory production of heterologous enzymes is described. High secretion efficiency of the novel SP sequence was applicable for both cell‐surface display and secretory production of cellulolytic enzymes (BGL and EG) in S. cerevisiae . In addition, the utilization of SED1 SP successfully enhanced the secretory production of BGL in Pichia pastoris .